Comparative analysis of the bryophyte floras of northwest Belarus concrete fortification and the Carpathians - dr. Sakovich, Anastasia; Rykovsky, Gennadij (Biodiversity: Research and Conservation, 2012)
The detailed research of bryophyte flora, carried out in 2008-2011 on fortifications from the times of the First World War and Second World War in Grodno district, resulted in recording 101 species, of which 95 species were true mosses (Bryophyta) and 6 species were hepatics (Marchantiophyta). Because the substratum displayed certain ecological similarity with carbonate rocks, we made comparative analysis of the species list. The total of 28 rare and very rare (in Belarus scale) bryophyte species were recorded, of which 3 species were included in the Red Data Book of Belarus; 3 species had a conservation status at the European level.